Follow up of Patients with Parathyroid Adenoma Detected by Parathyroid Scan (Bangladesh Journal of Nuclear Medicine, 2018)
Background: Primary hyperparathyroidism (PHPT) is the third most endocrine disorder after diabetes and thyroid disease. The objective of this study was to observe the outcome of those patients who had positive parathyroid scan with Technetium-99m (99mTc) sestamibi scan  referred to National Institute of Nuclear Medicine & Allied Sciences (NINMAS) to perform parathyroid scan.Patients and Methods: This longitudinal observational type of study was carried out at NINMAS, from January 2016 to December 2016. A total number of 43 hyperparathyroid patients who had positive parathyroid scan were included in this study during one year follow up period. There clinical status, biochemical profile & treatment history were evaluated Chi-quire and paired t-test were used to analyze the variables.Results: Among 43 study patients, number of male patients was 26 (60.5%) and female patients were 17 (39.5%). The mean ± SD age was 42.44 ± 12.11 years and majority was in age group 41-50 years. It was observed that 40 (93.0%) patients were symptomatic and only 3 (7.0%) were asymptomatic. Regarding symptoms, majority (81.4%) patients had bone pain followed by renal stone (58.1%). More than half (55.8%) patient had abdominal pain or cramps. Twenty nine (67.4.0%) patients undergone operation and 14 (32.6%) patients did not receive operative treatment at the one year follow up period.  Among 43 patients 29 (67.4%) were operated and all operated patients relieved their symptoms whereas patients 14 (32.6%) had not undergone operation and their symptoms persisted. There was strong statistical significant association (P